Anticancer effects of combined gamma-tocotrienol and 13-cis retinoic acid against neuroblastoma cells and xenografts - Ch'ng, Qin Ting (2021)
High-risk neuroblastoma mainly affects young children and is known to be resistant to treatment (surgery and chemotherapy) which is often attributed to amplified MYCN. Overexpressed Bcl-2 protein is also frequently a feature of neuroblastoma tumours. 13-cis retinoic acid (13cRA) is used as a differentiation agent in the final, maintenance stage of therapy to reduce recurrence of malignant tumours. However, response to this treatment is still not optimal due to side effects and treatment failure. Gamma-tocotrienol (γT3) has been found to induce apoptosis in neuroblastoma cells by binding to the BH3 groove of the Bcl-2 protein. It has also been investigated for its synergistic effects when used in combination with other drugs. This study had several aims. First, to explore the potential for a synergistic effect of γT3 and 13cRA used in combination for neuroblastoma, in vitro and in vivo. The mechanism of action by which γT3 acts in neuroblastoma will also be investigated. We investigated the effect of γT3 and/or 13cRA treatment on SH-SY5Y and SK-N-BE(2) cell lines and found that while individual treatments produced significant reduction in cell viability and increase in cell death, the addition of γT3 reduced the IC50 of 13cRA by more than half in both cell lines. Combination index values of <1 indicate that the combination of γT3 and 13cRA is synergistic. In the in vivo work, we found that the combination of γT3 and 13cRA significantly reduced tumour volume compared to other treatments (p≤0.05), including the specific Bcl-2 inhibitor, ABT-263. Annexin-FITC/PI flow cytometry showed increased population of apoptotic cells in the γT3 combination group in both cell lines, although it was not statistically significant compared to other treatment groups. Finally, protein expression studies were conducted using Bcl-2, Bcl-xL, MYCN, caspases-3 and -9 and p53. No conclusive changes were found when compared to other treatment groups from both in vitro and in vivo samples. In conclusion, the combination of γT3 and 13cRA showed significant anti-tumour effects on neuroblastoma, in vitro and in vivo. So, γT3 could potentially be used in combination with 13cRA, in a clinical setting. Further work is needed to confirm the mechanism of action.